Genetic variation in F2 populations and their potential in the improvement of grain yield in tef (Eragrostis tef) - Tefera, H.; Belay, G.; Assefa, K. (Springer, 2008)
Tef is a staple cereal of Ethiopia in high demand by consumers. In order to cope up with this high consumer demand, productivity per unit of land must increase through the development and use of high-yielding varieties. To this effect, the National Tef Research Project has long been striving towards the development of high yielding varieties through direct selection from germplasm and concentrating favourable alleles through hybridization and selection, despite the tedious crossing technique. The objective of this study was to assess the degree of genetic variation in F2 populations of tef as a basis for improving grain yield. F2 populations from 12 crosses and their parents were grown at the Debre Zeit Agricultural Research Center, Ethiopia, and assessment was made on eight traits on individual plant basis. Eleven of the 12 crosses showed substantial genetic variation for grain yield and its components, indicating the potential for improvement through selection. Moreover, grain yield, plant weight and yield related traits showed moderate to high heritability values (17–80%). In all the crosses, tiller number, panicle weight, yield per panicle and panicle length showed significant (P ≤ 0.05) and positive association with grain yield. Considering the degree of genetic variation and heritability values, emphasis should be given to selected crosses in an effort to developing high-yielding tef varieties.